Calculation of thermomechanical stresses and deformations in a reactor ampoule device with lithium ceramics under neutron irradiation - Chikhray, Ye.V.; Zaurbekova, Zh.A.; Askerbekov, S.K. (Recent Contributions to Physics, 2023)
Reactor experiments remain one of the few available methods for evaluating the performance of promising functional materials for fusion reactors under conditions of simultaneous exposure to neutron and gamma radiation, a gaseous environment, and thermal loads. Testing under neutron irradiation together with the application of numerical simulations (Finite Element Method) can lead to a complete understanding of the complex mechanical behavior of packed layers of pebbles by relating the macroscopic response of the infill to the microscopic interactions in a single pebble.The objective of this paper is describing the procedure and results of modeling of thermomechanical stresses and deformations that occur in the pebble bed of ceramic balls and in the irradiation device housing, in which the studied ceramic samples are placed during irradiation at the WWR-K reactor (Almaty, Kazakhstan).Calculation results show that ceramic pebbles, densely filled into the capsule of the WWR-K irradiation device so that they cannot move inside the filling, when heated to 1073K, will undergo thermomechanical loads from 10 to 80MPa, which exceeds the ultimate strength of 60MPa of ceramics Li4SiO4. The share of pebbles, the load on which exceeds the tensile strength, will be from 5 to 10% of their total number. In this case, the capsule will move down by 1-2mm, and expand by 200 microns radially under the influence of thermal elongation of the steel vacuum tubes connecting the capsule to the mounting flange. The strength of the tubes will not be affected.At a certain value of external pressure, the pebbles will abruptly move ("jump") into the empty area above the pebble bed, reducing the pressure on the remaining pebbles. It is not possible to describe such behavior within the framework of this model. The above calculations are relevant for the case of compacted pebble bed of lithium ceramics under neutron irradiation.A possible way to avoid the potential destruction of ceramic pebbles is to reduce the thickness of the capsule wall by 2-3 times, which will lead to an increase in the plasticity of the capsule walls, a decrease in the wall pressure on the pebble bed, and a decrease in the heating temperature of the capsule and ceramics.
Keywords: simulation; lithium ceramics; pebble bed; deformations